Evaluation of Adipokines: Apelin, Visfatin, and Resistin in Children with Atopic Dermatitis - Edyta Machura; Maria Szczepanska; Katarzyna Ziora; Dariusz Ziora; Elzbieta Swietochowska; Małgorzata Barc-Czarnecka; Alicja Kasperska-Zajac (Hindawi Limited, 2013)
Very little is known about the role of adipokines in atopic dermatitis (AD) in children. This study aimed at analyzing the serum levels of resistin, apelin, and visfatin in children with AD in relation to body weight, AD severity, and gender. Serum concentration of adipokines was measured in 27 children with AD and in 46 healthy subjects. Selected biochemical parameters were evaluated and skin prick test was performed. Serum levels of resistin and apelin were significantly higher, whereas serum visfatin concentration was significantly lower in children with AD versus healthy controls, although an increase in resistin levels was exclusively demonstrated in boys. In AD group, a significant increase in apelin levels in girls was documented. There was no relationship between adipokines levels and the degree of allergic sensitization. Receiver operating characteristic curve analysis demonstrated that the serum apelin cutoff value differentiating children with AD from those without was >137.8 pg/mL. Resistin and visfatin cutoff values were >3.8 ng/mL and ≤ 2.13 ng/mL, respectively. Apelin and visfatin can serve as excellent indicators to distinguish children with AD from those without disease.